How does digital trade impact women traders? - Renee N. Russo (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
This paper explores the potential opportunities and challenges digital trade poses for women traders globally and in Asia-Pacific. This paper highlights policy areas using a gendered approach to digital trade. Given the varied and interrelated issues, a public-private-societal effort is needed to help women traders. A mixed methods research approach to conduct situation analysis is used in this paper. It predominantly reviews existing literature, supported by descriptive statistics. A feminist economics lens and intersectional analysis are primarily used to examine how women's ability to leverage digital technologies for trade varies and how to improve it through policy changes. At the sociocultural level, education and technology exposure are critical to increase women's digital readiness and community acceptance of digital trade. These programs must target women and the broader community to destigmatise technology. Financial barriers, such as the cost of ICTs can be addressed through decreasing loan requirements and bolstering community safety net funds. [...]
hdl:20.500.12870/7107
Keywords: F10; F23; I18; J16; J18; J24; J70; L26; N75; O10; O17; O30; 330; Women; MSME; Global Value Chains; multinationals; global supply chains; Asia-Pacific